2014
DOI: 10.1007/s11103-014-0265-y
|View full text |Cite
|
Sign up to set email alerts
|

The B″ regulatory subunit of protein phosphatase 2A mediates the dephosphorylation of rice retinoblastoma-related protein-1

Abstract: The phosphorylation of plant retinoblastoma-related (RBR) proteins by cyclin-dependent kinases (CDKs) is well documented, but the counteracting phosphatases have not been identified yet. We report here that rice retinoblastoma-related protein-1 (OsRBR1) interacted with the B″ subunit of rice protein phosphatase 2A (OsPP2A B″) and underwent reversible phosphorylation during the cell division cycle. The OsRBR1-OsPP2A B" association required B domain in OsRBR1 and the C-terminal region of OsPP2A B″. We found by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Consistent with this, previous proteomic analysis identified the interaction between shugoshin and the isoforms of the B56 regulatory subunits of PP2A [ 70 ]. While this mechanism requires loss of PPP2R5D to cause decrease in pRb as we observed (Figure 6D ), previous studies have also shown that PP2A can also control the phosphrylation status of CDKs, perhaps Cdk2-CyclinE and/or Cdk4-CyclinD that are known to maintain the phosphorylation of Rb [ 71 , 72 ]. Thus, PPP2R5D loss may indirectly mediate a decrease in Rb phosphorylation.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with this, previous proteomic analysis identified the interaction between shugoshin and the isoforms of the B56 regulatory subunits of PP2A [ 70 ]. While this mechanism requires loss of PPP2R5D to cause decrease in pRb as we observed (Figure 6D ), previous studies have also shown that PP2A can also control the phosphrylation status of CDKs, perhaps Cdk2-CyclinE and/or Cdk4-CyclinD that are known to maintain the phosphorylation of Rb [ 71 , 72 ]. Thus, PPP2R5D loss may indirectly mediate a decrease in Rb phosphorylation.…”
Section: Discussionsupporting
confidence: 61%
“…Although RBR has been described as dephosphorylated by PP2A in rice, PP1s seem to be the major contributors in pRb and RBR dephosphorylation (Kolupaeva & Janssens ; Ábrahám et al . ). This observation leads us to suggest that RSS1 might act on cell cycle control/RBR pathway through the inhibition of PP1 to maintain meristems under stressful conditions, and therefore to ensure survival and return to growth once the stress is relieved.…”
Section: Interplay Between Rss1‐like Control Of Meristem Maintenance mentioning
confidence: 97%
“…Phosphorylation of B″ by a CDK increases its affinity to the PP2A holoenzyme, increasing dephosphorylation of OsRBR1. This is thought to be a mechanism that contributes to the inactivation of OsRBR1 during the cell cycle [ 54 ].…”
Section: Roles and Functioning Of B Subunitsmentioning
confidence: 99%